2014
DOI: 10.1371/journal.pone.0102303
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Wild-Growing Vitis amurensis ICE1 and ICE2 Encode MYC-Type bHLH Transcription Activators that Regulate Cold Tolerance in Arabidopsis

Abstract: Winter hardiness is an important trait for grapevine breeders and producers, so identification of the regulatory mechanisms involved in cold acclimation is of great potential value. The work presented here involves the identification of two grapevine ICE gene homologs, VaICE1 and VaICE2, from an extremely cold-tolerant accession of Chinese wild-growing Vitis amurnensis, which are phylogenetically related to other plant ICE1 genes. These two structurally different ICE proteins contain previously reported ICE-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 67 publications
2
51
0
Order By: Relevance
“…A similar phenomenon occurs in grape: overexpression of VaICE1 or VaICE2 in Arabidopsis could up‐regulate CBF transcript levels under control conditions (Xu et al . ). Further study is required to investigate the relationship between transcription activity of SmICE1a and cold tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…A similar phenomenon occurs in grape: overexpression of VaICE1 or VaICE2 in Arabidopsis could up‐regulate CBF transcript levels under control conditions (Xu et al . ). Further study is required to investigate the relationship between transcription activity of SmICE1a and cold tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…Two types of enzyme, ProDH and P5CDH, function in the degradation of proline (Cecchini et al, 2011). A previous study has demonstrated that overexpression of bHLH increases the proline content in transgenic Arabidopsis; however, the authors did not investigate whether bHLH regulates the expression of genes related to proline metabolism (Xu et al, 2014). The results of the present study showed that the transcript levels of AtbHLH112 were positively correlated with the expression of both P5CS genes, but negatively correlated with the expression of ProDH and P5CDH under salt and osmotic stress conditions (Fig.…”
Section: Researchmentioning
confidence: 98%
“…These findings support the inference that ICE1 has a function in regulating the expression of CBF and COR genes under cold stress, and that ICE1 and ICE2 together contribute even more to the cold‐induced gene expression and freezing tolerance. In addition, a role of ICE1 homologs in cold stress response has been observed in many plant species such as rice, tomato, Zea mays, Chrysanthemum dichrum , Chinese wild Vitis amurensis, Pyrus ussuriensis, Poncirus trifoliata , and Cucumis sativus (Liu et al 2010; Feng et al 2013; Xu et al 2014; Huang et al 2015a, 2015b; Lu et al 2017; Zhang et al 2017).…”
Section: Accession Numbermentioning
confidence: 99%